أثر الألعاب الالكترونية في السلوك و التحصيل الدراسي للتلميذ - يوسف بن منصور; عبد الرحمان قاوي; غربي عبلة (My University, 2023)
The aim of this study is to identify the extent of the impact of electronic games on the behavior and academic achievement of the student. The study adopted the following questions: -1Do electronic games affect the behavior of the middle school student? -2What is the effect of electronic games on the academic achievement of the middle school student? And it was answered with: -1Electronic games affect the behavior of the middle school student. -2Frequent practice of electronic games negatively affects the academic achievement of the middle school student. Keywords: academic achievement, behaviour, electronic games - intermediate education, student